PENERAPAN MULTIMEDIA MODEL SIMULASI DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI KELAS VII SMP NEGERI I ULUBONGKA KABUPATEN TOJO UNA UNA - Kariasi, Karnila (JSTT, 2016)
The research was conducted in the second semester in class VII SMPN I Ulubongka Tojo Una Una district number of students 21 he who consisted of 12 students, male and 9 female students. The school year 2014-2015. The purpose of the study was to describe the activities and learning outcomes of students of class VII SMPN I Ulubongka Tojo Una Una District after a given a learning science by using Multimedia. The method used descriptive method problem with classroom action research design according to Kemmis and Mc. Taggart with two cycles. Each cycle consists of two meetings. The results showed that the activity of the first cycle of students meeting the value 62,50%, the second cycle II meeting be 69,64%,and the second cycle ofÂ  meetings I scored 80,36%,the second cycle II meeting be 91,07%. Student learning outcomes with preetest 52,52%,Absorption classical first cycle of meetings I value I 66,33%,the first cycle of meetings II value 70,76%, cycle II meeting I value 78,95%,the second cycle II meeting be 85,76%. Mastery learning classical first cycle of meetings I value 23,81%, the first cycle of meetings II value 66,67%, cycle II meeting I value 88,71%, the second cycle II meeting tobe 100%.Increased student learning outcomes in the first cycle to the value ofÂ  N-Gain 0,14 (low) but then increased again to 0,30 (moderate) in cycle 2. Thus, it was cocluded that the application of multimedia in Learning Natural Science results can increase the activity and student learning in class VII SMPN I Ulubongka Tojo Una Una District.